Performance of crossbreed fattened calves in commercial farms in Spain - G. Domingo; A. Iglesias; J. Cantalapiedra; I. Blanco-Penedo; R. Payan-Carreira; L. Monserrat; L. Sanchez (Journal of Animal and Plant Sciences, 2014)
In the present study, parameters related to animal performance and carcass quality were evaluated in order to technically characterize crossbreed calves under commercial farm conditions. Sixty-six male calves of Holstein Frisian crossed with Rubia Gallega (n=43; 65.15%), Limousine (n= 16; 24.24%) and Belgian Blue-White (n=7; 10.61%) were used, in a ratio representative for the beef industry of the area. Nutrition and husbandry practices were identical for all the animals. All the calves were slaughtered at the age of 8 months.  Results indicated that the Belgian Blue-White crosses were the heaviest, more compact and with the best body conformation, and also a better carcass performance. On the contrary Limousine crosses showed the leanest carcass and the lowest performance. The carcasses of Rubia Gallega crosses showed intermediate characteristics. No statistically significant differences were found in the fatness content between the three genotypes.
Keywords: beef crosses; slaughtered age; commercial farms; morphometric characters; carcass traits